Acute viral gastroenteritis in children hospitalized in Iksan, Korea during December 2010-June 2011 - Cheol Whoan So; Dong Sup Kim; Seung Taek Yu; Ji-Hyun Cho; Jong Duck Kim (Korean Pediatric Society, 2013)
PurposeViral etiology is common in cases of children with acute diarrhea, and antibiotic therapy is usually not required. Therefore, it is important to determine the distribution of common viruses among children hospitalized with acute diarrhea.MethodsWe included 186 children who suffered from acute diarrhea and were hospitalized at the Wonkwang University Hospital Pediatric ward from December 1, 2010 to June 30, 2011 in this study. Stool samples were collected and multiplex reverse transcriptase polymerase chain reaction (multiplex RT-PCR) was used to simultaneously determine the viral etiology such as rotavirus, norovirus, astrovirus, or adenovirus.ResultsCausative viruses were detected in 72 of the 186 cases (38.7%). The mean age of the virus-positive cases was 1 year and 9 months (range, 1 month to 11 years). Rotavirus was detected in 50/186 (26.9%); norovirus, in 18/186 (9.7%); and astrovirus, in 3/186 cases (1.6%). Adenovirus was not detected in any of the cases. Proportions of norovirus genogroups I and II were 21.1% and 78.9%, respectively. Four of the 51 rotavirus-positive cases (7.8%) had received rotavirus vaccination at least once. The mean duration of diarrhea was 2.8 days (range, 1 to 10 days) and vomiting occurred in 39 of the 72 cases (54.2%).ConclusionViral etiology was confirmed in about one-third of the children with acute diarrhea, and the most common viral agent was rotavirus, followed by norovirus.